Изменения в пространственном распределении монгольской пищухи после обработки территории пестицидом - Крылова, Т.В. (Вестник зоологии, 1976)
Three-year observations of Ochotona pricei T h o m. after a single treatment of the territory with sevin showed that reduction in the number of animals caused deep population changes: local range of the animals reduction in density and degradation of the inhabited burrous.